Sanallisen arvioinnin sekä kodin ja koulun yhteistyökokeilun vaikutukset oppilaiden oppimistuloksiin = The experiment on verbal school reports and collaboration between home and school and its effects on pupils' learning results - Korpinen, Eira (1982)
The project is connected with the development of pupil evaluation. The report describes the effects of the experiment on pupils' learning results: study skills, motivation, self-concept, and achievement in mother tongue (3. grade) and mathematics (3. and 6. grade). The test group consisted of 543 pupils and the control group of 551. The theoretical background of the experimental programme was based on Beatty and Clark t s Self-Concept Theory of Motivation and Learning. Study skills improved most amongst low-achieving boys in grade 3 and in the subarea “study environment at home” it in grade 6. The experiment developed affective motivation in grade 3 and strengthened positive self-concept especially ''self-confidence and self-approval” in grade 6. The treatment influenced pupils' success in the dictation test in grade 3 and somewhat also their achievement in mathematics in grade 6.